Early Event-Related Potential During Figure and Object Perception of Abacus Mental Calculation Training Children: A Randomized Controlled Trial - Wang, Dong; Zhu, Kongmei; Cui, Jiacheng; Wen, Jianglin (Frontiers in Behavioral Neuroscience, 2022)
The aim was to discuss the impact of mental abacus calculation on the early processing of children’s perception on numbers and objects. Fourteen children received metal abacus calculation training (training group) and another 14 children did not receive training (non-training group) were randomly selected. The 28 subjects were asked to determine the figures and objects shown on the computer screen and recorded on the computer. A comparison was made about event-related potential component (N1, N170, P1, P2) of different brain areas between the two subject groups. The results showed occipital region P1 amplitudes of children who received mental abacus calculation training was larger than that of children who did not receive the training under the condition of figure stimulus （F=4.85,p<0.05）. The N1 potential period of children who received mental abacus calculation training was longer than that of children who did not receive the training（F=15.488，p< 0.01）. The N1 potential period of children who received mental abacus calculation training was longer than that of children who did not receive the training（F=13.37, p<0.01）. N170 amplitudes of children who received mental abacus calculation training was smaller than that of children who did not receive the training （F=12.98, p<0.0l）. P2 amplitudes of children who received mental abacus calculation training was smaller than that of children who did not receive the training （F=12.22，p<0．01）. Under the condition of object stimulus, the P2 potential periods of children who received mental abacus calculation training was longer than that of children who did not receive the training （F=8.41，p<0.01）. The activated degree of the occipital region of children who received mental abacus calculation training was enhanced, but the activated degree of the central region of the forehead and temporal occipital region was slightly down. Meanwhile, the potential periods of all components were extended. Therefore, long-term mental abacus calculation training can change children’s cortical function activities.